Potensi Wilayah Berbasis Sektor Pertanian Dalam Pembangunan Perekonomian Kabupaten Solok Selatan - Syahrial, Syahrial; Leovita, Angelia; Yuliana Putri, Olga (Jurnal Sosial Ekonomi Pertanian, 2024)
Determining strategic agricultural development in economic recovery requires determining the agricultural sector which is the leading commodity. This study aims to 1) analyze the leading commodities in the agricultural sector of South Solok Regency, 2) analyze the competitiveness of the main commodities of South Solok Regency, 3) analyze the specialization and localization of the main commodities of South Solok Regency. The study uses Location Quetient analysis, Localization Quotient, Specialization Quotation, Shift Share Analysis, and Dynamic Location Quetions. The results of the analysis show that 1) there are 18 superior commodities which are the basic of 28 agricultural sector commodities, 2) competitiveness in the district and province show equally prominent results, 3) agricultural sector commodities in South Solok Regency in each sub-district the reisno specialization and concentration. So the government needs to determine agricultural sector commodities that refer to the basic commodities of each commodity, and continue to support agricultural sector commodities that are basic but not a priority.